Methodological proposal for the management of Academic projects requirements in Research calls - VARGAS PÉREZ, LAURA SILVIA; FELIPE RIVERON, EDGARDO MANUEL; Jorge, Peralta-Escobar; María del C, Laurence-Santillán; Jose, Martínez-Flores; VARGAS PEREZ, VANESSA ATENEA (LACCEI, 2025)
In this research work, a methodology for a requirements organizing system based on requirements engineering techniques and project management standards is proposed, which allows monitoring and supporting the planning and managment of the requirements of projects participating in different academic calls for proposals issued by sponsoring organization for academic projects. As a case study, the research calls of the PRODEP a program for the Teacher Professional Development of the SEP (Secretaría de Educación Pública), of México was selected. This system will allow to understand and satisfy customer needs, the designers, to monitor and control their projects, from the beginning to the end. The methodology of a requirements organization system allows the assimilation of good practices in the areas of requirements engineering, information quality, among others.Project methodologies, Requirements organizer, Requirements engineering, Project management